Nas margens do rio Peruaçu: a apropriação da natureza e a natureza das práticas - Marília Raiane Rodrigues Silva (2021)
Through this investigation, we sought to identify ways to understand the effects of water scarcity, in the context of the Peruaçu river valley, a left bank tributary of the uppermiddle São Francisco. While some aspects of the territorial formation of the northern region of Minas Gerais were being unveiled, the motivations for the drought of the Peruaçu river were also outlined. As a methodological background, we operate a division of the Peruaçu basin into three different compartments – headwaters, midcourse and lowcourse to reflect on the geophysical, historicalsocial and technicalpolitical processes responsible for the partial drought of the river, as well as the effects of water scarcity in the context of maintaining life in the territory. The fieldwork, focused on different parts of the basin, served to stitch the analyzes together through interviews and participant observation, which are tributary methodologies of the ethnographic method. Although these three compartments present substantial differences between them (both from a geomorphological and sociospatial point of view), the transformations that take place in the different stretches of the river proved to be intimately interconnected. They are consequences of a contingency of factors, which are central to two main motivations: a) the reverberations, on a regional and local scale, of production processes linked to the agroindustrial exploitation of eucalyptus, which began in the 1970s and 1980s, whose main heritage they are land conflicts arising from land grabbing and the consequent social and environmental vulnerability; b) and, more recently, the forms of legaladministrative control of the territory by the State under conservation units, aimed at guaranteeing the protection of its cultural and environmental heritage. The confluence of these two models of land appropriation reveals an agency character of technicalpolitical and vital transformations in space. Although drought presents itself as the main problem for the maintenance of local life, networks of actors operate on the margins of these transformations and are making concrete responses to the need for water maintenance.